The Role of Citizenship Education in Building Bantul Community Political Participation in The Pandemic Covid 19 - T Heru Nurgiansah (Universitas Sebelas Maret, 2021)
This research aims to establish the political participation of Bantul people through citizenship education at the pandemic of Covid 19. The political participation of Bantul society needs to be improved so that the apathy towards politics is not increasingly faded. There are many ways to establish the political participation of Bantul people through the role of citizenship education. This method of research uses a qualitative approach. Data collection techniques use observations, interviews and literacy studies. The result of this study mentions that citizenship education has an important role and succeeded in establishing the political participation of Bantul people in the pandemic of Covid 19.